Comparative proteomic analysis of pathogenic and non-pathogenic strains from the swine pathogen Mycoplasma hyopneumoniae - Klein Cátia S; Zaha Arnaldo; Pinto Paulo M; Ferreira Henrique B (Proteome Science, 2009)
Abstract Background Mycoplasma hyopneumoniae is a highly infectious swine pathogen and is the causative agent of enzootic pneumonia (EP). Following the previous report of a proteomic survey of the pathogenic 7448 strain of swine pathogen, Mycoplasma hyopneumoniae, we performed comparative protein profiling of three M. hyopneumoniae strains, namely the non-pathogenic J strain and the two pathogenic strains 7448 and 7422. Results In 2DE comparisons, we were able to identify differences in expression levels for 67 proteins, including the overexpression of some cytoadherence-related proteins only in the pathogenic strains. 2DE immunoblot analyses allowed the identification of differential proteolytic cleavage patterns of the P97 adhesin in the three strains. For more comprehensive protein profiling, an LC-MS/MS strategy was used. Overall, 35% of the M. hyopneumoniae genome coding capacity was covered. Partially overlapping profiles of identified proteins were observed in the strains with 81 proteins identified only in one strain and 54 proteins identified in two strains. Abundance analysis of proteins detected in more than one strain demonstrates the relative overexpression of 64 proteins, including the P97 adhesin in the pathogenic strains. Conclusions Our results indicate the physiological differences between the non-pathogenic strain, with its non-infective proliferate lifestyle, and the pathogenic strains, with its constitutive expression of adhesins, which would render the bacterium competent for adhesion and infection prior to host contact.